2023
DOI: 10.3390/ijerph20043397
|View full text |Cite
|
Sign up to set email alerts
|

A Telehealth Home-Based Exercise Program for Community-Dwelling Older People with Dementia in Indonesia: A Feasibility Study

Abstract: (1) Background: This study aimed to evaluate the feasibility of a telehealth home-based exercise program for older people with dementia living in Indonesia with support from their informal carers. (2) Methods: Pre–post intervention single group study with three assessment time-points (baseline, 12 and 18 weeks). Participants with dementia underwent a 12-week physiotherapist-delivered telehealth exercise program, with informal carer supervision between supervised online sessions, and continued the exercises for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…Participants acknowledged benefits of the online-delivered exercise program on physical and psychological health of the people with dementia. The benefits reported in this qualitative study align with objective outcomes from this study ( Sari et al, 2023a ), including improved physical activity levels, improvement in some aspects of function and disability, exercise enjoyment and quality of life. Other studies on online-delivered exercise programs have also reported benefits, including increasing levels of moderate physical activity in both people with dementia and their carers ( Ptomey et al, 2019 ) and improved falls efficacy for the person with dementia ( Taylor et al, 2020 ).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Participants acknowledged benefits of the online-delivered exercise program on physical and psychological health of the people with dementia. The benefits reported in this qualitative study align with objective outcomes from this study ( Sari et al, 2023a ), including improved physical activity levels, improvement in some aspects of function and disability, exercise enjoyment and quality of life. Other studies on online-delivered exercise programs have also reported benefits, including increasing levels of moderate physical activity in both people with dementia and their carers ( Ptomey et al, 2019 ) and improved falls efficacy for the person with dementia ( Taylor et al, 2020 ).…”
Section: Discussionsupporting
confidence: 76%
“…The flow diagram of participant recruitment, withdrawals, and exclusions is shown in Figure 1 . In our feasibility study from which participants for interviews were recruited ( Sari et al, 2023a ), 30 people with dementia and their 30 family carers, and 10 paid carers were involved. Of these, only 12 of the 30 people with dementia were deemed able to participate in the interview process, while 26 family carers, and 4 paid carers involved in part or all of the 12-week online-delivered exercise program were interviewed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 outlines the characteristics of 14 eligible studies, with eight originating from the United States [ 16 , 27 33 ], two from Australia [ 17 , 34 ], and one each from Germany [ 35 ], Korea [ 36 ], Taiwan [ 37 ], and Brazil [ 38 ]. Among these, nine were quantitative studies (including three RCTs [ 31 , 36 , 37 ], five pre-post intervention studies[ 16 , 27 , 28 , 33 , 34 ], and one cross-sectional design [ 38 ]), three were qualitative studies [ 29 , 32 , 35 ], and two were mixed-method studies, one of which was a pre-post intervention design [ 30 ], and the other a randomized controlled crossover design [ 17 ]. Seven studies were pilot studies [ 16 , 17 , 27 30 , 33 ].…”
Section: Resultsmentioning
confidence: 99%